FRAKSI ETANOL RIMPANG JERINGAU (Acorus calamus L.) SEBAGAI ANTIBAKTERI RERHADAP Staphylococcus aureus DAN Escherichia coli - Pratika Viogenta; Nopiyansyah Nopiyansyah; Fitri Fitri (Fakultas MIPA Universitas Tulang Bawang Lampung, 2018)
Acorus calamus L. (jeringau) rhizomes are one of the medicinal plants used as traditional medicine in Indonesia. This plant were used as an antibacterial. The purpose of this research were to prove the inhibition jeringau rhizome on the selected microorganisme including two bacterial trains Staphylococcus aureus and Escherichia coli. The rhizomes of jeringau were extracted with maceration method using ethanol 70 % and fractionation process using solvent v/v (ethanol, n-hexane and chloroform). The antibacterial activity used the cup plate method with the concentration 20%, 40%, 60%, 80%, and 100%, positive control using ampicillin and negative control using aquades. The test were continved by determining the minimum inhibitor concentration (MIC). Research was obtained zone diameters of 0 mm (negative control), 35.37 mm (positive control), 23.33 mm (concentration 20%), 25.52 mm (40%), 27.11 mm (60%), 30.09 mm (80%), and 33.16 mm (100%) against Staphylococcus aureus. Inhibitory zone diameters 0 mm negative control, 36.68 mm positive control, 22.53 mm (concentration 20%), 25.85 mm (40%), 28.08 mm (60%), 29.73 mm (80%), and 32.21 mm (100%) against Escherichia coli. The minimum inhibitory concentration (MIC) value in both bacterial were 2%. The results showed that all fraction concentrations could inhibit the growth of Staphylococcus aureus and Escherichia coli. Keywords : Rhizome Jeringau, Staphylococcus aureus, Escherichia coli.